Application of the K-Means Clustering Algorithm to the Case of Stunting Risk Families in Districts/Cities of West Sumatra Province in 2023 - Widiyanti; Fitri, Fadhilah (Mathematical Journal of Modelling and Forecasting, 2024)
Stunting is one of the indicators of chronic nutritional status that has a long-term effect on child growth; the main contributing factors are households that do not have access to clean drinking water, proper sanitation facilities, and other factors. The adverse effects experienced by stunted children are reduced cognitive ability, learning ability, decreased endurance, and can lead to new diseases such as diabetes, heart disease, and many other diseases. This study uses the K-Means Cluster method to group the Regency / City of West Sumatra Province in 2023 regarding cases of stunting risk families. K-Means Cluster analysis is an analysis used to group data based on similar features or characteristics. From the results of the study, it can be concluded that the clustering of 19 regencies/cities in West Sumatra Province resulted in 2 groups (clusters): cluster 1 consists of 12 regency/city members, and cluster 2 consists of 7 regency/city members. The characteristic results obtained from each cluster formed are cluster 2 shows families with better conditions than cluster 1.